Martin Eden [videorecording (DVD)] - Marcello, Pietro, 1976-; Marcello, Pietro, 1976-; Marcello, Pietro, 1976-; Marinelli, Luca; Cressy, Jessica; Nemolato, Vincenzo; London, Jack, 1876-1916 (Kino Lorber, 2021)
A working class writer hopes that his literary aspirations will help him rise to a different social class and marry a rich young woman.